Language Styles and Dharma Presentation Techniques in the Writings of Pra Maha Sompong Talaputto - นวลศิริ, สัญรญา; สัตโยภาส, สนิท; พูลพิพัฒน์, นราวัลย์ (Ganesha Journal, 2018)
The objective of this article was to investigate the language styles and Dharma presentation techniques in ten writings of Venerable Phra Maha Sompong Talaputto. The analytical description was used to present the study results. The study findings revealed that three language styles were used by the author, namely, word choice, sentence choice, and the use of proverbs, expressions and sayings. For the word choice, it was found that words with closely similar meanings were used the most. For the sentence choice, conditional sentences were found to be the most frequent. For the use of proverbs, expressions and sayings, three types were discovered: using existing proverbs, expressions and sayings; modifying original proverbs, expressions and sayings; and inventing new ones. Regarding the various and discrete presentations of his teachings, four techniques were found: creating the titles, opening the stories, presenting the stories, and closing the stories. As for creating the titles, theme-based titles were used most frequently. Opening the stories by directing to the main points was utilized the most. Giving examples was mostly used for presenting the stories. Finally, summary of main ideas was used the most for closing the stories.